The Influence Of Competency And Communication On Employee Work Effectiveness At The Regional Population Control And Family Planning Service Of South Tapanuli Regency - Abdul Latif Lubis; Ali Mukti Tanjung; Budi Alamsyah Siregar; Ahmad Karim (Yayasan Multidimensi Kreatif, 2025)
Employee work effectiveness is a crucial factor in determining the success of an organization, particularly in government agencies. Competence and communication are two key aspects that play a role in improving the quality of employee performance. This research was conducted at the Population Control and Family Planning Office of South Tapanuli Regency to determine the extent to which these two variables influence work effectiveness. The results are expected to contribute to human resource development and more optimal organizational governance. The objectives of this research are: To determine the partial and simultaneous influence of competence and communication on employee work effectiveness at the Population Control and Family Planning Office of South Tapanuli Regency. The problem statement is: To what extent do competence and communication partially and simultaneously influence employee work effectiveness at the Population Control and Family Planning Office of South Tapanuli Regency? The research method used a quantitative method with 33 respondents from the Population Control and Family Planning Office of South Tapanuli Regency. Data analysis was performed using SPSS Version 23. Research Results: 1). The results show that competence has a positive and significant effect on employee work effectiveness. The contribution of competence to work effectiveness is reflected in the Beta value of 0.475 or 47.5%. This finding strengthens the theory that knowledge, skills, and work attitudes are the main keys in improving organizational performance. Thus, improving employee competence is a strategic factor for achieving optimal work effectiveness. 2). In addition, the results of the study also show that communication has a positive and significant influence on employee work effectiveness. The contribution of communication to work effectiveness is reflected in the Beta value of 0.410 or 41.0%. This finding confirms the importance of communication in creating understanding, coordination, and harmonious work relationships. With open, clear, and effective communication, employees can work more focused, efficient, and productive. 3). Simultaneously, competence and communication are proven to have a significant influence on employee work effectiveness. The coefficient of determination (R Square) value of 0.782 indicates that both variables are able to explain the variation in work effectiveness by 78.2%, while the remaining 21.8% is influenced by other factors outside this study. This finding proves that the third hypothesis is acceptable. The combination of adequate competence and effective communication is the main determinant of employee success in carrying out their duties. These two variables complement each other, with competence providing capacity and work quality, while communication fosters coordination, understanding, and collaboration. Given their significant contributions, improving employee work effectiveness requires strategies to strengthen competence and improve communication systems within the organization.